Scholarships, fellowships and loans : a guide to education-related financial aid programs for students and professionals - Miskelly, Matthew; Thomson Gale (Firm); Gale (Firm) (Detroit : Thomson Gale, 2008)
Collects and provides application information for over six thousand sources of educational financial aid, including local, state, and federal loans and scholarships
Federal programs -- AmeriCorps -- State higher education agencies -- Abbreviations -- Sponsors and their scholarships -- Field of study index -- Legal residence index -- Place of study index -- Special recipient index -- Sponsor and scholarship index
Keywords: Scholarships -- United States -- Directories; Student loan funds -- United States -- Directories